On Genetic Improvement of Trees for Social Forestry in India - Rajora, G. P.; Zsuffa, L. (Indian Forester, 1986)
We propose that genetic improvement of the multi-purpose tree species must play leading role in a social forestry program in India and will benefit the community at the earliest. The possibilities and prospects for genetic improvement of social forestry tree species are high as demonstrated in India and elsewhere. Basic principles of forest genetic, are well-established and apply equally to industrial plantations and social forests. However, in social property. There is the added factor of interaction with agriculture crops. The features desirables for social forestry plantations in Indla are quantity and quality of fuel and fodder, nitrogen fixation and soil stabilization abilities. Resistance to disease, drought, cold and urban stress. These features could be signficantly improved by various conventional tree improvement methods such as matching species and provenances with site and end use, selection, breeding and seed orchard establishment, and unconventional methods such as mutation breeding and genetic engineering. Genetically improved material should be cloned for mass propagation Multiple trait section will be needed because simultaneous improvement in several characteristics is required. The test designs should be management specific. Initially the tree improvement activities should be concentrated on few multi-purpose native tree species and this paper lists some of them with climatic zones and major uses. Tree improvement work on social forestry species could be taken up at the Forest Research Institute, Dehra Dun in collaboration with various national and international agencies.